The Amityville horror - Douglas, Andrew; Bay, Michael (Sony Pictures Home Entertainment; distributed in the Philippines by D'Corcorde Recording Corporation, 2005)
A horror film about a young couple and their children who move into a house that was once the site of a horrific series of murders. Over the next 28 days, they find that the house might be haunted by a murderous presence.